Flat electrode diameter effect on glow discharge structure and properties - Lisovskiy, V.A.; Osmayev, R.O.; Yegorenkov, V.D. (Вопросы атомной науки и техники, 2019)
This paper is devoted to studying the effect of flat electrode diameter values on current-voltage characteristics and axial structure of the glow discharge in nitrogen. We have demonstrated that the discharge current increases with the electrode diameter growing. One has to apply a considerably higher voltage across small electrodes than across large ones to transport one and the same current. The discharge structure evolves at the current fixed in such a way that a thinner cathode sheath forms near the small cathode, the negative glow length is substantially larger, and the positive column is shorter than in the case of employing large diameter electrodes. In the negative glow we have observed maxima in the axial profiles of the emission lines of nitrogen molecules and ions measured with the optical spectrometer. On moving away from the cathode, the line intensities decrease uniformly till the positive column indicating the presence of fast electrons not only in the negative glow but also in the dark Faraday space.